2011
DOI: 10.1042/bj20111240
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical role of the collagen-rich tumour microenvironment in pancreatic cancer progression

Abstract: PDAC (pancreatic ductal adenocarcinoma) is among the most deadly of human malignances. A hallmark of the disease is a pronounced collagen-rich fibrotic extracellular matrix known as the desmoplastic reaction. Intriguingly, it is precisely these areas of fibrosis in which human PDAC tumours demonstrate increased expression of a key collagenase, MT1-MMP [membrane-type 1 MMP (matrix metalloproteinase); also known as MMP-14]. Furthermore, a cytokine known to mediate fibrosis in vivo, TGF-β1 (transforming growth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
175
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(178 citation statements)
references
References 170 publications
2
175
0
1
Order By: Relevance
“…20,[44][45][46] In addition, the detection of aligned collagen signatures in routine histopathology slides can predict disease 16 In pancreatic ductal adenocarcinoma, cancer cells in contact with collagen type I show enhanced migratory capabilities through upregulation of Snail, a regulator of epithelial-to-mesenchymal transition. [47][48][49][50][51] Epithelial-to-mesenchymal transition is a process that dissemination-competent cells undergo. It has been shown to be prevalent in pancreatic ductal adenocarcinoma tissue and to negatively impact patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…20,[44][45][46] In addition, the detection of aligned collagen signatures in routine histopathology slides can predict disease 16 In pancreatic ductal adenocarcinoma, cancer cells in contact with collagen type I show enhanced migratory capabilities through upregulation of Snail, a regulator of epithelial-to-mesenchymal transition. [47][48][49][50][51] Epithelial-to-mesenchymal transition is a process that dissemination-competent cells undergo. It has been shown to be prevalent in pancreatic ductal adenocarcinoma tissue and to negatively impact patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with adjacent normal pancreatic tissue, PDAC tumors demonstrate increased fibrosis and increased numbers of activated myofibroblasts in the fibrotic microenvironment (6)(7)(8). As a recent report showed that the BET family protein BRD4 mediates the profibrotic response in activated liver stellate cells (13), we evaluated human PDAC tumors for BRD4 expression.…”
Section: Bet Inhibitors Decrease Collagen I Production By Primary Pscmentioning
confidence: 99%
“…Pancreatic stellate cells (PSCs) are the predominant fibroblasts present in the pancreas and the key regulators of fibrosis in vivo (7,12). In the quiescent state, PSCs demonstrate cytoplasmic lipid droplets and produce minimal amounts of collagen I and other extracellular matrix (ECM) proteins (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly relevant in pancreatic cancer, where cancer progression is marked by the fibrotic nature of the ECM surrounding and throughout the tumor [26]. This fibrotic ECM is dense and stiff and requires high pericellular MMP activity in order for cells to invade through it suggesting that this disease might be sensitive to specific MMP-14 inhibition as an approach to block invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%